PENGARUH CITRA MEREK DAN KEMASAN RAMAH LINGKUNGAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN STARBUCKS DI SURAKARTA) - Evi Nur Aini; Sri Walyoto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of brand image and green packaging on consumer purchasing decisions. The population in this study is Starbucks consumers in Surakarta. The research method used in this research is quantitative. The sampling technique used was non-probability sampling, namely random sampling, with a total sample of 115 respondents. The data were analyzed using the SPSS 23 program. The dependent variable of this study was purchasing decisions. The independent variables were brand image and green packaging. The results showed that: (1) brand image had a significant effect on purchasing decisions, and (2) green packaging had no significant effect on purchasing decisions.